Bank Mergers Performance and the Determinants of Singaporean Banksâ Efficiency: An Application of Two-Stage Banking Models - Sufian, Fadzlan; Abd. Majid, Muhamed-Zulkhibri (Gadjah Mada International Journal of Business, 2007)
An event study window analysis of Data Envelopment Analysis (DEA) is employed in this study to investigate the effect of mergers and acquisitions on Singaporean domestic banking groupsâ efficiency. The results suggest that the mergers have resulted in a higher post-merger mean overall efficiency of Singaporean banking groups. However, from the scale efficiency perspective, our findings do not support further consolidation in the Singaporean banking sector. We find mixed evidence of the efficiency characteristics of the acquirers and targets banks. Hence, the findings do not fully support the hypothesis that a more (less) efficient bank becomes the acquirer (target). In most cases, our results further confirm the hypothesis that the acquiring bankâs mean overall efficiency improves (deteriorates) post-merger resulted from the merger with a more (less) efficient bank. Tobit regression model is employed to determine factors affecting bank performance, and the results suggest that bank profitability has a significantly positive impact on bank efficiency, whereas poor loan quality has a significantly negative influence on bank performance.